Separation of Long Double-Stranded DNA by Nanoparticle-Filled Capillary Electrophoresis - Huang, Ming-Feng; Kuo, Yi-Chun; Huang, Chih-Ching; Chang, Huan-Tsung (Analytical chemistry (Washington), 2004)
We present the first example of the analysis of long double-stranded (ds) DNA molecules by nanoparticle-filled capillary electrophoresis (NFCE). To avoid aggregation of the gold nanoparticles (GNPs) and to allow strong interactions with the DNA molecules, the gold nanoparticles were modified with poly(ethylene oxide) (PEO) via noncovalent bonding to form gold nanoparticle/polymer composites (GNPPs). The neutral GNPPs are heavy (∼2.0 × 108 g/mol for the 32-nm GNP) and thus slow the DNA molecules that they encounter during the electrophoretic process. Compared to linear polymer solutions, such as hydroxyethyl cellulose and PEO, the GNPPs provide greater efficiency and require significantly shorter times to separate long dsDNA. The separation of λ-DNA (0.12−23.1 kbp) by NFCE at −250 V/cm was accomplished in 3 min. The ability to separate high molecular weight DNA markers (8.27−48.5 kbp) with plate numbers greater than 106 suggests that this novel method may hold great promise for the analysis of long-stranded DNA molecules such as chromosomes. Moreover, this method is simple and affordable when compared to those that use micro- and nanofabricated devices for separating long DNA molecules.